PENGARUH PARIWISATA TERHADAP PENINGKATAN PENDAPATAN PEDAGANG KAKI LIMA (PK5) DI PANTAI LOSARI MAKASSAR - Ikram, Muhammad; Saharullah, Saharullah (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This research is aimed to increase the income of pavement (PK5) in Pantai Losari Makassar. The method or type of this study is the population or target survey that is the tourists and experts on the beach losari losari, each of 20 people. Techniques of writing data through questionnaires, interviews and materials as a supporter. Data analysis was done by using simple linear regression analysis.Working hypothesis: Release and train have a significant effect on increasing the income of the street vendors in losari beach. The result of analysis based on result of simple linear regression analysis obtained y = 5,787 + 0,910x. And by partial test or partial determination coefficient (r2). To increase the income of PK5 beach losari makassar by 0,522. Through F test obtained Fcount of 19.690 which means for income increase PK5, and simultaneously (r2) is equal to 52,27%. This means that the increase of PK5 in coastal losari makassar is 68.8% by tourists and 47.72% by other factors that are not in the analysis.